Energy Transition Pathways for the 2030 Agenda in Asia and the Pacific - Nations Unies (United Nations, 2018)
The Asia and the Pacific region has become a global economic powerhouse. The region’s rapid and sustained economic growth, increasing population, expanding industrialisation and rapid urbanization are driving rapid growth in energy demand, which. Ensuring that supplies of energy are adequate to meet the growth in demand in ways that are socially, economically and environmentally responsible creates a new set of challenges for policymakers. The transition to 2030 energy pathway, which is aimed at addressing those challenges, has four coherent and interlinked objectives – increased energy supply to meet the growing demand, improved energy security, meeting the SDG7 targets and achieving NDCs. Addressing the complex and challenging task requires policymakers to develop a clear, sustainable and achievable pathway that would enable the countries, as well as the region as a whole, to achieve the 2030 goals and targets This report undertakes an in-depth analysis to first determine the level of achievement is possible under the current policy regime by developing a baseline. It then identifies the gap between the baseline and the 2030 targets to inform policymakers the additional efforts and resources that would be needed to adequately achieve SDG7 targets as well as the NDCs mitigation targets for the energy sector. Finally, different transition pathways have been developed and their socio-economic and environmental facets have been examined to assist policymakers to make an informed decision. The report also identifies the enabling policy, technology and market environment that would accelerate the achievement of the 2030 targets.